Interação intraguilda entre Chrysoperla externa (Hagen) e Hippodamia convergens (Guérin-Meneville) e suas implicações no controle de pulgões da roseira - Tamashiro, Luiza Akemi Gonçaves (2016)
Roses are the most cultivated and consumed throughout Brazilian territory. In pest management, employment of sustainable control methods, as biological control, has become an efficient alternative method for various crops and ornamentals grown in greenhouses. The species Chrysoperla externa (Hagen, 1861) (Neuroptera: Chrysopidae) and Hippodamia convergens (GuerinMeneville, 1842) (Coleoptera: Coccinellidae) are important biological control agents as they exhibit desirable characteristics, such as voracity and high efficiency in prey searching. As a strategy to optimize pest population suppression, use of more than one natural enemy may be employed once they together can be more effective. On the other hand, the control of pest population can be compromised by negative interaction, such as intraguild predation. This study aimed to evaluate the predatory capacity of Rhodobium porosum (Sanderson, 1901) and Macrosiphum rosae (Linnaeus, 1758) (Hemiptera: Aphididae), as well as the influence of intraguild interaction of this predators in the control of these aphids on rose cultivation. Leaf blades werefirstly infested with standardized age of R. porosum and M. rosae, followed by the release of a single second-instar nymph of each species of predator. After 24 hours, number of consumed nymphs was estimated and as well as the mortality of predators when released together. The predatory behavior was analyzed for one hour using the software Etholog 2.2. The highest consumption by C. externa and H. convergens was observed for first-instar nymphs as preys, followed by secondand third-instar nymphs for the two aphid species. The older predators get, the more they consumed aphid nymphs, with the highest consumption rate on the last day of assessment. Intraguild predation just occurred in the treatments with no prey, resulting in a mortality of 70% of H. convergens. In the treatments where preys were present, predators interacted positively, promoting a higher consumption when they were together than when released individually. In regard to the behavior pattern, a longer time spent by C. externa and H. convergens preying was observed when they were together than individually. In the absence of prey, longer time spent in searching and standing still was verified for the predators, indicating change in the behavior because of the presence of the other predator species.